Evaluation for hard endosperm, bird-proof sorghum [(Sorghum bicolor L. (Moench)] and its effect on food quality - Shiringani, Amukelani Lacrecia (University of the Free State, 2005)
Grain sorghum is an important cereal crop for food security in developing countries. The crop is mainly preferred due to its adaptability to harsh environments including extreme temperatures and water limiting environments. However, for grain sorghum to compete equally with maize, certain improvements must be made. The objectives of the study were to measure the 1) yield potential of genotypes 2) identify bird-resistance genotypes 3) compare Group I and Group III genotypes in terms of food quality characteristics. Thirty genotypes including two standards, developed by the Agricultural Research Council, Potchefstroom, South Africa were used. These genotypes were planted in Potchefstroom and Taung, in the North West province of South Africa. The experiment was laid out in a randomized complete block design with three replications. Data collected for yield potential included grain yield, seed weight per panicle, full panicle weight, and thousand seed mass. Data was analyzed per location and across locations using Agrobase, 2000. The results showed highly significantly differences among genotypes in the locations and across locations in all yield characteristics measured. The interaction between entry and location was highly significant. Genotypes were evaluated for bird resistance through the percentage grain yield loss. Percentage bird damage was highly significantly different between groups and among genotypes in Potchefstroom. The damage was severe in group I compared to group III. Taung resulted in 100% bird damage. Two hundred and fifty gram per sample was assessed in a Tangetial Abrasive Dehulling Device for abrasive hardness index (AHI), followed by milling and flour color assessment. The samples were not replicated except for endosperm texture, and grand means were used to compare the groups. Group I performed better than group III in terms of milling yields, flour color, AHI, percentage kernel removed and endosperm texture. These milling quality characteristics showed significant correlation with each other and most importantly correlated with endosperm hardness. Therefore, many food quality characteristics in sorghum are determined by endosperm texture. A 12% solution (flour and water) was used to analyze viscosity of the porridge using the Brabender ® Viskograph ‘E’. The response of genotypes during cooking showed highly significant differences. Groups were highly significantly different for maximum viscosity, start of cooling period, breakdown, and setback and non-significant for beginning of gelatinization, end of cooling period, and end of final holding. Viscosity parameters measured were positively correlated to each other.

Graansorghum is ‘n belangrike graangewas vir voedselsekuriteit in ontwikkelende lande. Die gewas word verkies omdat dit aangepas is in marginale toestande met hoë temperature en vogstremming. Maar vir graansorghum om te kompeteer met mielies moet daar sekere verbeterings gemaak word. Die doelwitte van hierdie studie was om te bepaal 1) Wat die opbrengspotensiaal van die genotipes is 2) Of daar voël weerstandige genotipes is 3) Om Groep I en Groep III genotipes te vergelyk vir hulle voedselkwaliteits eienskappe. Dertig genotipes, insluitend twee standaarde, wat ontwikkel is deur die Landbou Navorsingsraad, Potchefstroom, Suid Afrika, is gebruik. Die genotipes is geplant in Potchefstroom en Taung, in die Noordwes provinsie van Suid Afrika. Die eksperiment is uitgelê as ‘n gerandomiseerde blokontwerp met drie herhalings. Data wat versamel is om opbrengspotensiaal te meet is graanopbrengs, saadmassa per panikel, vol panikel massa en duisend saad massa. Data is geanaliseer per lokaliteit en oor lokaliteite met Agrobase98 LAN. Die resultate het hoogs betekenisvolle verskille tussen genotipes binne en tussen lokaliteite aangetoon vir alle gemeette eienskappe.Die interaksie tussen inskrywing en lokaliteit was hoogs betekenisvol. Genotipes is geëvalueer vir voël weerstand deur persentasie graanverlies te bepaal. Persentasie voëlskade was hoogs betekenisvol verskillend tussen groepe en tussen genotipes vir Potchefstroom. Die skade was baie hoog in groep I genotipes in vergelyking met die in groep III. Taung het 100% voëlskade gehad. Tweehonderd en vyftig gram per monster is geëvalueer in ‘n “Tangetial Abrasive Dehulling Device” om abrasie hardheids indeks te bepaal (AHI), gevolg deur maal em meelkleur assessering. Hierdie analises is nie gerepliseer nie, behalwe die endosperm hardheid, en die gemiddeldes is gebruik om groepe te vergelyk. Group I het beter presteer as groep III in terme van maal opbrengs, meelkleur, AHI, persentasie van die sade verwyder en endosperm tekstuur. Hierdie maaleienskappe was betekenisvol met mekaar gekorreleer en dan baie belangrik was dit met endosperm hardheid gekorreleer. Daarom kan heelwat kwaliteitseienskappe afgelei word van die endosperm tekstuur. ‘n Twaalf persent oplossing (meel en water) is gebruik om viskositeit te analiseer van pap met ‘n Brabender ® Viskograph ‘E’. Die verskille tussen genotipes tydens die kookproses was hoogs betekenisvol. Groepe was ook hoogs betekenisvol verskillend vir maksimum viskositeit, begin van afkoelingstyd, afbreek, and omkeer maar nie betekenisvol vir begin van gelatinisering, einde van afkoeling, en die finale houtyd nie. Die viskositeits eienskappe was positief met mekaar gekorreleer.
Dissertation (M.Sc. (Plant Sciences (Plant Breeding))--University of the Free State, 2005
Keywords: Kafir corn as food; Kafir corn -- Genetics; Kafir corn -- Evaluation